Rendemen dan Skrining Fitokimia Simplisia Daun Bayam (Amaranthus viridis) - Norhayati; Rizaldi, Gusti; Noorwina, Syifa; Anida (Universitas Borneo Lestari, 2024)
Indonesia is rich in biodiversity. One of the plants that grows widely in Indonesia is spinach (Amaranthus viridis). The aim of this research was to determine the secondary metabolite content of the ethanol extract of spinach leaves (A. viridis) qualitatively. This research consisted of 2 stages. The first stage is making simplicia and the second stage is screening phytochemical simplicia. The yield obtained from making simplicia was 20.83%. Based on the results, it can be concluded that spinach leaves (A. viridis) contain secondary metabolites of alkaloids, tannins, phenols, and saponins. The suggestion for this research is that the secondary metabolites can be isolated and then continued with activity tests.